A comprehensive review of partial opioid agonists for the treatment of chronic pain. Issue 3 (September 2020) - Gress, Kyle; Charipova, Karina; Jung, Jai Won; Kaye, Alan D.; Paladini, Antonella; Varrassi, Giustino; Viswanath, Omar; Urits, Ivan
Abstract : Chronic pain is a common condition that is being increasingly recognized, diagnosed, and treated in a variety of settings. Opioids can be used to treat chronic pain but at the cost of adverse effects and risk of dependence. Recently, there has been a movement to improve analgesic care in the setting of the opioid epidemic and the overprescribing of opioids, causing over-accessibility, dependence, and large numbers of overdose deaths. Opioid-specific receptors, including the μ, δ, κ, and opioid receptor like-1 (ORL-1) receptors, are each 7-transmembrane spanning proteins, which affect the G-protein and β-arrestin cascades. Each opioid class can act differently on the receptors, resulting in full, partial, or antagonizing effects. This comprehensive review looks at different agents in major classes, nonselective and mixed/partial agonists/antagonists, including the nonselective partial agonists, levorphanol and tramadol. Mixed partial agonists/antagonists include buprenorphine, pentazocine, nalbuphine, and butorphanol. Oliceridine is the only current selective partial agonist that agonizes specific pathways to promote analgesic effects and discourage adverse effects.